حركة البيورتان الاصلاحية في إنكلترا خلال عهد الملكة اليزابيث1533-1603 - ظاهر مشعل مفرح; مغتاظ ماريا حسن (lark, 2019)
Abstract This research deals with the subject of reformist religious topics important in the history of England and especially during the reign of Queen Elizabeth (1533-1603) that presents sometimes in the framework of the political dimension and at other times in the context of religious and intellectual dimension. Politically began religious reform reacts and growing and growing presence with the growing problem of religious divisions and the many beliefs that clashed with each other and have been associated with politics and the power of kings, where, as Queen Elizabeth declared that religious unity condition indispensable for the stability of the general situation of the country. The religious and intellectual side and through the perception of Protestantism, especially those The Puritan, since these asked cleared the church of all that holds the impact of the Catholic Church, whether in faith or even in the form of religious or ecclesiastical bodies rituals. The Puritan found its way among all strata of society Englishman, who expressed the preference The Puritan attack on the Episcopal order and rituals of the Catholic ideas, and they considered a bulwark against the growing Catholic. The Queen Elizabeth position first of The Puritan position tolerant as it announced its respect personal religious views, provided that they leave for public order of the state, and not Prejudice the country’s security and unity of the nation, and thus allowed The Puritan participate in the political life and enter the parliament and the establishment of religious congregations semi-autonomous, but increased its political clout and religious called the Queen to put an end to the growing activities in the country through the issuance of laws and stop their publications to limit the growth of their activity, and after that launched an attack on the Anglican Church, which consider The Puritan no different from the Catholic Church, completely contradictory with the first Christian church, Asked The Puritan through parliament on reforms in several laws including a book public prayers for the year 1559, trying to do to convince the Queen and the government with their ideas of reform in parliament, but to no avail prompting them to break away from the English church and formed their own teams, and thus became the national conflict with the Queen and with the Anglican Church .